Fgf10 Signaling in Lung Development, Homeostasis, Disease, and Repair After Injury - Yuan, Tingting; Volckaert, Thomas; Chanda, Diptiman; Thannickal, Victor J.; De Langhe, Stijn P. (Frontiers in Genetics, 2018)
The lung is morphologically structured into a complex tree-like network with branched airways ending distally in a large number of alveoli for efficient oxygen exchange. At the cellular level, the adult lung consists of at least 40-60 different cell types which can be broadly classified into epithelial, endothelial, mesenchymal, and immune cells. Fibroblast growth factor 10 (Fgf10) located in the lung mesenchyme is essential to regulate epithelial proliferation and lineage commitment during embryonic development and postnatal life, and to drive epithelial regeneration after injury. The cells that express Fgf10 in the mesenchyme are progenitors for mesenchymal cell lineages during embryonic development. During adult lung homeostasis, Fgf10 is expressed in mesenchymal stromal niches, between cartilage rings in the upper conducting airways where basal cells normally reside, and in the lipofibroblasts adjacent to alveolar type 2 cells. Fgf10 protects and promotes lung epithelial regeneration after different types of lung injuries. An Fgf10-Hippo epithelial-mesenchymal crosstalk ensures maintenance of stemness and quiescence during homeostasis and basal stem cell (BSC) recruitment to further promote regeneration in response to injury. Fgf10 signaling is dysregulated in different human lung diseases including bronchopulmonary dysplasia (BPD), idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD), suggesting that dysregulation of the FGF10 pathway is critical to the pathogenesis of several human lung diseases.